Redes de organizações esportivas: gênese e evolução - Colagrai, Alexandre Conttato (2015)
Sport is a social event and as such is articulated in networks, because society is a network. This study intended to analyze how emerge and evolve the organization network of sports nonprofit organizations that develop the sport according to sporting events established by Pelé Law, which are: educational sports, sports participation and high performance sport, and check if this network is a strategic resource for sports organization face difficulties in its operating environment. For such a qualitative survey was conducted. Interviews were conducted with two managers of each organization, in order to identify whether they recognize the network of your organization as it emerged and evolved, and this network is an important resource for the development of the organization. It was also applied a questionnaire to these managers, to obtain data on the relationships networking of organizations, seeking to understand with whom they relate, where the level of dependency of these organizations with respect to network organizations, and the frequency of monthly contacts between them. They were also carried out interviews with people participating in the activities offered by the sports organizations, in order to check if they recognize any organization's network. Studies have been conducted on the websites of organizations, and visits to local activities, seeking to understand how the presence of network organizations in these spaces. Interview data were analyzed using the Atlas IT software for better understanding and categorization of information and questionnaire data were entered into the VOSVIEWER software for the description of the network, allowing viewing it. The results show the sports organizations relating to network and these networks have emerged spontaneously and have a level of evolution of a self-organized network. This network is configured as a strategic resource for sports organizations face challenges in its operating environment.